#TITLE_ALTERNATIVE# - OCTOVINA WOSPAKRIK, MARIANETTE
This final year project discusses the emission of gravitational waves from compact binary systems at the in-spiral phase before their coalescence. In the first part, the basic theory of gravitational waves involving the general relativity formalism of its propagation, generation, and radiation from binary system is discussed. In the next part, the post-Newtonian method, the post-Minkowskian method, and other approximation methods which can be used to obtain the multipole moments of the compact binary system are discussed. After obtaining the approximation formalism for each moment, this formalism is then applied to the compact binary system to compute the total energy flux and the orbital phase up to the 3.5PN order, and gravitational wave polarization up to the 2.5PN order. In the final part, the accuracy of the derived formalism is tested by applying the formalism to the binary systems of PSR 1913+16 and PSR J1756-2251. The calculation results of orbital period show that the post- Newtonian formalism gives the value which is in the same order as the values obtained from the observation, that is ~10 degree -1 day.